Resprouting of Woody Saplings Following Stem Snap by Wild Pigs in a Malaysian Rain Forest - Ickes, Kalan; Dewalt, Saara J.; Thomas, Sean C. (The Journal of ecology, 2003)
1 The lowland rain forest at Pasoh Forest Reserve in Peninsular Malaysia is subject to disturbance by native wild pigs (Sus scrofa). Female pigs snap off woody plants up to 3.5 m tall to construct nests for reproduction, damaging > 170 000 saplings$\text{km}^{-2}\ \text{year}^{-2}$. We investigated the ability of 1808 woody saplings to survive and resprout over a 3-year period following pig and experimental stem snap. 2 Most plants resprouted to some degree, but, in understorey conditions, growth of new shoots was slow. More than 90% of stems were alive 3 months after damage, but > 40% had not yet produced a single fully expanded leaf. Mortality at 36 months was higher for resprouting saplings (33%) than for undamaged control saplings (9%). Survival of damaged stems was highly and positively correlated with stump basal diameter. Canopy species consistently showed lower survivorship than midstorey, understorey and treelet species but no differences in survivorship were found for habit (tree vs. liana) or leaf morphology (simple vs. compound). 3 The number and total length of resprout shoots (TSL) were strongly, positively correlated with stump diameter. Canopy species produced greater TSL but fewer new shoots than did smaller-stature species. Trees and lianas produced similar TSL at 3 and 6 months, but trees produced more TSL at 12 and 36 months. Simple-leaved plants consistently had longer TSL than compound-leaved plants. 4 Both species and families differed greatly in terms of survival, TSL and number of shoots. Dipterocarpaceae, which comprises 24% of basal area in the forest, and Euphorbiaceae, the most species-rich family, had especially poor survivorship of damaged individuals. 5 Our results suggest that elevated pig densities found in small forest reserves such as Pasoh are likely to alter tree community composition as a result of the differential ability of species to regenerate following physical disturbance. Regeneration of canopy tree species, particularly in the silviculturally important and heavily dominant family Dipterocarpaceae, may be particularly susceptible to pig-related disturbance.